Automatic Machine of Distributed Fish Feed Based on Arduino Uno - Sentot Novianto; Supriyadi; Abigunto Amoro Adji; Larasati Rizky Putri; Rangga Komara; Amrullah Gilang; Jesika Erventy; Maria Stevanie Dwi; Aditya Pradika; Ezra Halomoan (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The need for feed in fish-keeping ponds is vital for the survival of the fish that are kept. Some fishpond farmers still provide fish feed manually and it is felt to be inefficient. On the other hand, the focus of farmers can be focused on maintaining fishponds. This PKM activity utilizes appropriate technology as an automatic feed tool for spreading tilapia fish feed. The driving of this feed is connected to a controller which functions to regulate the spreader of tilapia feed regularly and the design is made to achieve the spread of tilapia feed with a large capacity of 50 kg each e day. The use of this tool was conducted in tilapia fish maintenance/cultivation using ponds/ponds on land. The placement location is in the Karawang sub-district, West Java.